Identification of DAP3 as candidate prognosis marker and potential therapeutic target for hepatocellular carcinoma - Yuan, Liu-Xia; Yue, Zhi-Qiang; Ma, Qin-Rong; Zhang, Peng; Xiao, Feng; Chen, Lin (Frontiers in Immunology, 2025)
BackgroundAmong malignant tumors, hepatocellular carcinoma (HCC) is both prevalent and highly lethal. Most patients with advanced-stage liver cancer have a poor prognosis. Death-associated protein 3 (DAP3) is reportedly related to tumors and may hold great promise for the future.MethodsDAP3 transcriptome data along with related clinical information were obtained from The Cancer Genome Atlas (TCGA), GEO, and ICGC databases. We assessed its prognostic value, clinical relevance, associated pathways, immune infiltration, gene mutations, and sensitivity to chemotherapeutics. A prognostic risk model was subsequently developed and evaluated using receiver operating characteristic (ROC) curves and Kaplan-Meier (KM) plots. Additionally, a nomogram was created and validated through calibration and decision curve analysis (DCA). Furthermore, quantitative real-time PCR (qRT-PCR), Western blot, and immunohistochemical (IHC) staining were performed to examine the expression of DAP3 in HCC. Finally, gene knockdown and overexpression experiments, along with cell counting kit-8 (CCK-8) assays, colony formation assays, and tests for cell apoptosis, migration, and invasion, were conducted to investigate the role of DAP3 in HCC.ResultsThe study discovered that DAP3 expression was linked to HCC subtypes, and its high expression was linked to a poor prognosis. There were significant differences in immune infiltration level, mutation level, prognostic value and chemotherapeutic efficacy. Subsequently, we constructed a prognostic model and demonstrated that high risk score was significantly related to a poor survival rate. A predictive nomogram demonstrated that the nomogram model was effective prediction tool that can accurately predict the survival rate of patients with different clinical characteristics. Additionally, DAP3 expression significantly increased in both tissue samples and cell lines. Elevated levels of DAP3 were correlated with larger tumor size and higher alpha-fetoprotein (AFP) levels, and Cox analysis confirmed that DAP3 was a clinically independent prognostic marker. Finally, cell assays revealed that the knockdown of DAP3 significantly impeded cell proliferation and metabolic activity and induced apoptosis. Conversely, the overexpression of DAP3 had opposite effects on these cellular processes.ConclusionsOur study on DAP3 can provide a reference for HCC diagnosis, treatment and prognosis assessment.